Respuesta :
(-3) *(5 x -6 y) =(-38) *(-3)
5 * (3 x +4 y ) = 0 * 5
You will have
-15 x +18 y = 114
15 x +20 y =0
you add 2 equations together
You will have
38 y =114
y=3
Then you chance y =3 in equation 2, you will have
3 x +4 *3 =0
3 x = -12
x = - 4
You have x= -4 and y = 3
(-4,3)
5 * (3 x +4 y ) = 0 * 5
You will have
-15 x +18 y = 114
15 x +20 y =0
you add 2 equations together
You will have
38 y =114
y=3
Then you chance y =3 in equation 2, you will have
3 x +4 *3 =0
3 x = -12
x = - 4
You have x= -4 and y = 3
(-4,3)
The solution to the equation is (3, -4)
Simultaneous equation
Given the system of equation
- 5x − 6y = −38 ....... 1 * 3
- 3x + 4y = 0 ...... 2 * 5
The equation will become:
15x - 18y = -114
15x + 20y = 0
Subtract
-18y - 20 y = -114
-38y = -114
y = 3
Since 3x + 4y = 0
3x + 4(3) = 0
3x + 12 = 0
3x = -12
x = -4
Hence the solution to the equation is (3, -4)
Learn more on simultaneous equation here: https://brainly.com/question/16863577